1999
DOI: 10.1161/01.hyp.34.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Contracting Factor in Carotid Artery of Hypertensive Dahl Rats

Abstract: Abstract-The present study is designed to investigate whether acetylcholine (ACh) elicits an endothelium-derived contracting factor (EDCF) and whether it contributes to decreased relaxant response induced by ACh in Dahl rats. Dahl salt-sensitive (DS) and -resistant (DR) rats were fed a 0.4% NaCl or an 8% NaCl diet for 4 weeks. High sodium intake significantly increased blood pressure in DS rats but not in DR rats. The carotid rings were suspended for isometric tension recording. ACh caused an endothelium-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
(30 reference statements)
2
17
1
1
Order By: Relevance
“…49 Enhanced formation of 8-isoprostane has been associated with several cardiovascular risk factors 50 and has been found to correlate with in vivo thromboxane A 2 biosynthesis. 39,45 In line with these reports, we previously reported that high salt induces acetylcholine-induced contraction caused by endotheliumderived contraction factor, which may be thromboxane A 2 and/or prostaglandin H 2 , in carotid and renal arterial rings but not aorta of hypertensive DS rats, 19 and L-arginine supplementation diminished the contraction. 20 Actually, we showed in this study that high salt loading increases urinary thromboxane B 2 (a stable metabolite of thromboxane A 2 ) excretion ( Figure 7B), which was reduced by L-arginine supplementation.…”
Section: Discussionsupporting
confidence: 71%
“…49 Enhanced formation of 8-isoprostane has been associated with several cardiovascular risk factors 50 and has been found to correlate with in vivo thromboxane A 2 biosynthesis. 39,45 In line with these reports, we previously reported that high salt induces acetylcholine-induced contraction caused by endotheliumderived contraction factor, which may be thromboxane A 2 and/or prostaglandin H 2 , in carotid and renal arterial rings but not aorta of hypertensive DS rats, 19 and L-arginine supplementation diminished the contraction. 20 Actually, we showed in this study that high salt loading increases urinary thromboxane B 2 (a stable metabolite of thromboxane A 2 ) excretion ( Figure 7B), which was reduced by L-arginine supplementation.…”
Section: Discussionsupporting
confidence: 71%
“…Increased COX-2 prostanoids in hypertension Alvarez et al 775 Prostanoids acting on TP receptors have been described as implicated in the altered response to several vasoconstrictors in aorta from different animal models of hypertension [2,3,21,34,35]. In agreement, the TP receptor blocker SQ 29,548 reduced the phenylephrine-induced contraction in segments from both strains, and this reduction was markedly greater in aorta from SHR, as also occurred with indomethacin, NS 398 and dexamethasone.…”
Section: Discussionmentioning
confidence: 89%
“…However, neither furegrelate nor OKY 046, both TxA 2 synthase inhibitors, modified the response to phenylephrine, suggesting that prostanoids other than TxA 2 , by acting on the TP receptor, contribute to the constrictor effect of phenylephrine on aortic segments. Contractile prostanoids other than TxA 2 have also been involved in the vasoconstrictor responses induced by angiotensin II in aorta from rats with aortic-coarctation-induced hypertension [34], while TxA 2 has been implicated in the contraction induced by endothelin [2], A23187 [2] and acetylcholine [35].…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Figure 2, the percentage of the area under the curve was greater after the exercise, suggesting that acute resistance exercise decreased the vasoconstrictor prostanoid release in conductance vessels. The endothelial dysfunction present in arterial hypertension evokes an increase in vasoconstrictor prostanoid production, 35-38 and a single resistance exercise session has an important impact on vascular function improvement, because it decreases the vasoconstrictor prostanoid release. Moreover, it is well established that NO can regulate the activity of COX enzymes 39 and the activity of NOS is increased when the COX pathway is inhibited by indomethacin.…”
Section: Discussionmentioning
confidence: 99%